(untitled) (Research, Society and Development, 2021)
Objective: to analyze the health care models provided in the care of women in situations of prison. Methodology: a descriptive, exploratory study with a qualitative approach carried out with the health professionals who attend the female prison in Alagoas. Results: despite all the advances in health care for women in situations of prison, a predominantly biomedical care model predominates, aimed at resolving / curing diseases and the main comorbidities presented by the demand for existing cases. This reality makes valid the discussion that structural changes and in the training of professionals are necessary to guarantee social reintegration and reintegration in its broadest and most effective concept. Conclusion: a preventive model in the recluse environment and its interference in the health-disease context contribute to the reduction of diseases, greater health promotion and increase in the quality of life, in such a way that the persistence in a biological assistance, centered on the cure of diseases, the reintegration of these women into social life.